(untitled) (Acta Scientiarum. Health Sciences, 2012)
There has been an increase during recent years in the use of pesticides in agricultural activities to improve productivity, reduce labor costs and increase profits. On the other hand, the use of pesticides in excess or without adequate biosafety practices could lead to serious harm to human health. Current research evaluated toxicity risks in the case of 50 agricultural workers from the São Paulo Rural Community in the municipality of Concordia, Santa Catarina State, Brazil, who were exposed to pesticides. The questionnaire with open- and closed-ended questions revealed that there are several situations and procedures that expose most farm workers to toxicity risks since they do not have a clear understanding of biosafety measures or suitable knowledge on the products they use. Since a lack of information on pesticides exists, there is strong evidence for measures to inform and raise consciousness so that agricultural workers may exercise self-care in handling pesticides.